Using decision quality principles to balance your R&D portfolio James E. Matheson and Michael M. Menke explain how to strike a balance between risk and return - Matheson, James E. and Michael M. Menke (Research management (Now: research technology management))
The same principles for improving the success of individual R&D projects are critical for balancing risk and reward in an R&D portfolio.